Krajowa Rada Sądownictwa w Polsce - Patyra, Sławomir (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article concerns the position of the National Council of the Judiciary in light of the Constitution of the Republic of Poland of 2 April 1997. The author analyses the constitutional basis for the functioning of this body and its tasks in safeguarding the independence of the courts and judges. The author draws attention to the changes that were introduced in the previous term of office of the Sejm with regard to the functioning of the National Council of the Judiciary. He criticises in particular the procedure for the election of judges to the National Council of the Judiciary by the Sejm, indicating that adopted regulations concerning this matter are inconsistent with the Constitution.
Keywords: Poland; National Council of the Judiciary; independence of judges; infringement of the Constitution